Consensus en conflict: een discussiedossier: Inleiding - van Dam, Petra J.E.M. (TSEG - The Low Countries Journal of Social and Economic History, 2023)
Publications on water management in medieval and early modern times usually focus on one or a few regions, but Consensus and Conflict covers the entire area of the Netherlands. The book by Milja van Tielhof addresses important questions as: who shaped water management? How could farmers and other landowners exert influence? How did landowners participate in decision-making and which groups, including non-landowners, had influence or were even represented in the water board? The editors of TSEG asked four historians to reflect on the book from their own areas of expertise. They endorse many conclusions, for example that the myth of the "democratic" water board is a thing of the past with this book, and that social relations left a strong mark on governance and management of water works. They also highlight underexposed themes, formulate new questions, argue for alternative visions and for (further) international comparison.